Association Between Emergency Medicine Clerkship Diversity Scholarships and Residency Diversity. Issue 3 (8th December 2020) - Duong, David K.; Samuels, Elizabeth A.; Boatright, Dowin; Wilson, Taneisha
Abstract: Objective: To improve resident diversity, emergency medicine (EM) residencies across the United States have implemented financial scholarships to attract visiting medical students underrepresented in medicine (URiM). The impact of these scholarships on changes in residency racial and ethnic diversity is currently unknown. In this study, we describe characteristics of these visiting elective scholarships for underrepresented students and evaluate changes in residency racial and ethnic diversity after program implementation. Methods: From 2018 to 2019, we conducted a cross‐sectional survey of EM residency programs with a visiting clerkship rotation scholarship for medical students URiM. Programs were identified for study inclusion using the Society for Academic Emergency Medicine's online directory of Visiting Elective Scholarship Programs for Underrepresented Minorities. Program characteristics were analyzed descriptively. Changes in residency racial and ethnic diversity were evaluated using an interrupted time series analysis. Results: Of 34 programs contacted, 20 responded. While there was some variability in funding sources, scholarship amounts, and application review, most scholarships were similar in implementation practices. Of the 20 program respondents, nine were able to provide complete data on residency race and ethnicity and were included in the time series analysis. After program implementation, the time series analysis showed a significant increase in both underrepresented minority EM residents overall and Black and Latinx EM residents in particular. Conclusion: Emergency medicine visiting clerkship scholarship programs for medical students URiM vary in funding type and application review but had similar implementation practices. Residency programs increased their racial and ethnic diversity after program implementation. Future investigations are needed to determine specific factors contributing to the successful implementation of scholarship programs.